Language Pedagogy and Identity. Learning from Teachers' Narratives in the Colombian ELT - Diego Fernando Ubaque-Casallas (Asociación Colombiana de Profesores de Ingles, 2021)
This article examined two English teachers' professional identities based on a series of interviews conducted in two universities in Bogotá, Colombia. This paper examined their experiences and discourses regarding language pedagogy. Accordingly, the study adopted a narrative methodology from a decolonial lens to put some tension on the normative conception of the traditional/hegemonic notions of pedagogy and teacher identities configured in the Colombian English Language Teaching (ELT) context. Findings revealed that teachers enact their language pedagogies by merging their personal selves with their professional ones. As a result, identities and ways of knowing are validated in negotiation between doing and being. This posture towards teaching exposes their ontological and epistemic struggles for humanizing their pedagogy.